ANALISIS STIMULASI PERKEMBANGAN MOTORIK KASAR ANAK USIA DINI 5-6 TAHUN DI TK AL IHSAN MEDAN PETISAH - Siti Wardhani; Roni Sinaga (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
Field phenomena show that stimulation of gross motor development in early childhood has been carried out in a planned manner and is part of the learning process at AL IHSAN Kindergarten, Medan Petisah. Children are involved in various activities related to body movement and physical activity, which indicates that there are efforts to develop gross motor skills in the school environment. This study aims to analyze how gross motor development is stimulated in early childhood 5-6 years old. The study used a descriptive qualitative method with two classroom teachers as subjects. Data were obtained through observation, interviews, and documentation, then analyzed using the crease-swell model. The results indicate that gross motor development stimulation in early childhood has been implemented effectively. Gross motor stimulation was carried out through various activities, including hopscotch, throwing a ball, zigzag running, jumping over a hoop, and passing a ball. With the encouragement given by the teacher, the child becomes more enthusiastic and provides reinforcement which makes the child more confident by giving rise to various responses according to the child's condition.